(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article focuses on the fact that ensuring road safety is directly related to the protection of the natural human right to life, that this task is the work of the Beowist state, the attention paid to this area by legislation and the international community, the current situation related to ensuring road safety in Uzbekistan. The author gives the idea of developing a concept of road safety for children and young people, while at the same time making suggestions about the work that should be carried out in the future in the field of road safety.